2018
DOI: 10.1002/ente.201700560
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Fast Pyrolysis of Bamboo over Micro‐mesoporous Composite Molecular Sieves

Abstract: To upgrade biocrude oils from biomass pyrolysis, a novel micro‐mesoporous composite molecular sieve with HZSM‐5 structure as the core and MCM‐41 structure as the shell is synthesized and utilized. The synthesized hierarchical catalyst is characterized using X‐ray diffraction, N2 adsorption–desorption measurements, and transmission electron microscopy. Catalytic fast pyrolysis of bamboo over the composite molecular sieve is implemented using quantitative pyrolysis‐gas chromatography/mass spectrometry (Py‐GC/MS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Several studies have reported the introduction of mesoporosity in ZSM-5 microcrystallite catalyst particles to facilitate enhanced access to catalytic sites. This can be done through multiple routes including the phase transformation of the ordered mesoporous structure of MCM-41 into ZSM-5 via recrystallization, partial desilication of large crystals of ZSM-5, and resilication in the presence of templating surfactants (cetyltrimethylammonium bromide, CTAB) to form hierarchical MCM-41/ZSM-5 composites or the preparation of core–shell ZSM-5/MCM-41 composites where a shell of MCM-41 is formed by adsorbing the templating surfactant on the external surface of crystals of ZSM-5 followed by MCM-41 nucleation. , While these methods lead to effective composites, they require multiple steps in composite synthesis and are difficult to scale up, and in the case of hierarchical composites formed by desilication and resilication to MCM-41, there is a loss of acid sites. , …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the introduction of mesoporosity in ZSM-5 microcrystallite catalyst particles to facilitate enhanced access to catalytic sites. This can be done through multiple routes including the phase transformation of the ordered mesoporous structure of MCM-41 into ZSM-5 via recrystallization, partial desilication of large crystals of ZSM-5, and resilication in the presence of templating surfactants (cetyltrimethylammonium bromide, CTAB) to form hierarchical MCM-41/ZSM-5 composites or the preparation of core–shell ZSM-5/MCM-41 composites where a shell of MCM-41 is formed by adsorbing the templating surfactant on the external surface of crystals of ZSM-5 followed by MCM-41 nucleation. , While these methods lead to effective composites, they require multiple steps in composite synthesis and are difficult to scale up, and in the case of hierarchical composites formed by desilication and resilication to MCM-41, there is a loss of acid sites. , …”
Section: Introductionmentioning
confidence: 99%
“…The partial crystallization of mesoporous molecular sieves with suitable acidity and good hydrothermal stability can boost their acid catalytic performance. [19][20][21][22][23][24][25][26][27] Relatively few reports focused on the preparation of micro-mesoporous molecular sieves by mesoporous wall crystallization, mainly due to the small pore wall thickness that is difficult to be completely crystallized. Huang et al, 28 synthesized the ZSM-5/MCM-41 composite molecular sieve by partially crystallizing the amorphous pore wall of MCM-41 through a two-step crystallization process, in which the crystallization time was controlled at the second step.…”
Section: Introductionmentioning
confidence: 99%